Splicing machinery is profoundly altered in systemic lupus erythematosus and antiphospholipid syndrome and directly linked to key clinical features. Issue 135 (February 2023) - Lopez-Pedrera, Ch; Patiño-Trives, A.M.; Cerdó, T.; Ortega-Castro, R.; Sanchez-Pareja, I.; Ibañez-Costa, A.; Muñoz-Barrera, L.; Ábalos-Aguilera, M.C.; Ruiz-Vilchez, D.; Seguí Azpilcueta, P.; Espinosa, M.; Barbarroja, N.; et al.
Abstract: Objectives: To characterize the splicing machinery (SM) of leukocytes from primary antiphospholipid syndrome (APS), systemic lupus erythematosus (SLE) and antiphospholipid syndrome with lupus (APS + SLE) patients, and to assess its clinical involvement. Methods: Monocytes, lymphocytes and neutrophils from 80 patients (22 APS, 35 SLE and 23 APS + SLE) and 50 HD were purified, and 45 selected SM components were evaluated by qPCR-microfluidic array. Relationship with clinical features and underlying regulatory mechanisms were assessed. Results: APS, SLE and APS + SLE leukocytes displayed significant and specific alterations in SM-components (SMC), associated with clinical features [autoimmune profiles, disease activity, lupus nephritis (LN), and CV-risk markers]. A remarkable relationship among dysregulated SMC in monocytes and the presence of LN in SLE was highlighted, revealing a novel pathological mechanism, which was further explored. Immunohistology analysis of renal biopsies highlighted the pathological role of the myeloid compartment in LN. Transcriptomic analysis of monocytes from SLE-LN(+) vs SLE-LN(−) identified 271 genes differentially expressed, mainly involved in inflammation and IFN-signaling. Levels of IFN-related genes correlated with those of SMC in SLE-LN(+). These results were validated in two external SLE-LN(+) datasets of whole-blood and kidney biopsies. In vitro, SLE-LN(+)-serum promoted a concomitant dysregulation of both, the IFN signature and several SMC, further reversed by JAKinibs treatment. Interestingly, IFNs, key inflammatory cytokines in SLE pathology, also altered SMC. Lastly, the over/down-expression of selected SMC in SLE-monocytes reduced the release of inflammatory cytokines and their adhesion capacity. Conclusion: Overall, we have identified, for the first time, a specific alteration of SMC in leukocytes from APS, SLE and APS + SLE patients that would be responsible for the development of distinctive clinical profiles. Highlights: Splicing machinery (SM) is significantly and specifically altered in primary APS, SLE and APS plus SLE leukocytes. Splicing machinery alteration is associated with disease activity scores, relevant clinical features and autoimmunity. Simultaneous alterations of SM and key transcriptional signatures were recognized in SLE patients' monocytes with nephropathy Serum inflammatory profile in SLE-LN(+) patients was found linked with both, leukocytes' IFN signature and altered SM. Ex vivo and in vitro studies identified the effects of either silencing or overexpressing key SMC on leukocyte activity.